Tunable Piezophotonic Effect on Core-Shell Nanoparticles Prepared by Laser Ablation in Liquids under External Voltage - A. K. Kodeary; S. M. Hamidi (Journal of Nanotechnology)
We report an experimental study on the piezophotonic effect of gold and lead zirconate titanate (PbZrTiO3) nanoparticles (NPs) and also their core-shell nanostructures prepared by the laser ablation in liquid method. To obtain these NPs and composite materials, the targets were immersed in deionized water and a polymeric solution of polyvinyl pyrrolidone (PVP) under Nd:YAG laser pulses irradiation. Linear and nonlinear properties of these NPs were studied by optical spectroscopy and the Z-scan technique. Furthermore, tunable nonlinear properties of the NPs were measured under an external electric field under illumination to investigate the piezophotonic effect. Our results show that, at the interface of PZT and Au, due to the Schottky barrier, we have electron/hole recombination prevention, which leads to efficient enhancement in the nonlinear properties.